2018
DOI: 10.1186/s13256-018-1849-y
|View full text |Cite
|
Sign up to set email alerts
|

Alectinib (Alecensa)-induced reversible grade IV nephrotoxicity: a case report and review of the literature

Abstract: BackgroundLung cancer is among the top causes of cancer-related mortality in men and is the second most common cancer after breast cancer in women. There are approximately 234,030 new cases of lung cancer and 154,050 deaths from lung cancer in 2018 as per the latest American Cancer Society’s report. Alectinib, a more potent orally active tyrosine kinase inhibitor which was approved by the US Food & Drug Administration for anaplastic lymphoma kinase-positive lung adenocarcinoma, has been shown to have a reasona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 9 publications
0
22
0
Order By: Relevance
“…While the Anaplastic Lymphoma Kinase (ALK) inhibitor Crizotinib has been reported to be associated with acute kidney injury and chronic kidney disease, [1][2][3] the association with Alectinib is less well defined and merits further elucidation. [4][5][6] Alectinib is a second-generation highly selective oral Anaplastic Lymphoma Kinase (ALK) inhibitor approved by the FDA as first line therapy in ALK positive Non Small Cell Lung Carcinoma (NSCLC) and as second line therapy to Crizotinib resistant NSCLC. 6 Phase one studies of Alectinib in ALK-positive NSCLC reported increases in serum creatinine in 26% of participants, 6,7 and previous cases reported a temporal relationship between initiation of Alectinib and deterioration in kidney function without any other discernable cause, which improved with cessation of the agent.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…While the Anaplastic Lymphoma Kinase (ALK) inhibitor Crizotinib has been reported to be associated with acute kidney injury and chronic kidney disease, [1][2][3] the association with Alectinib is less well defined and merits further elucidation. [4][5][6] Alectinib is a second-generation highly selective oral Anaplastic Lymphoma Kinase (ALK) inhibitor approved by the FDA as first line therapy in ALK positive Non Small Cell Lung Carcinoma (NSCLC) and as second line therapy to Crizotinib resistant NSCLC. 6 Phase one studies of Alectinib in ALK-positive NSCLC reported increases in serum creatinine in 26% of participants, 6,7 and previous cases reported a temporal relationship between initiation of Alectinib and deterioration in kidney function without any other discernable cause, which improved with cessation of the agent.…”
Section: Discussionmentioning
confidence: 99%
“…6 Phase one studies of Alectinib in ALK-positive NSCLC reported increases in serum creatinine in 26% of participants, 6,7 and previous cases reported a temporal relationship between initiation of Alectinib and deterioration in kidney function without any other discernable cause, which improved with cessation of the agent. [4][5][6] The degree of kidney dysfunction varied across reported cases ranging from mild kidney injury to severe kidney injury requiring renal replacement therapy. 4 Nagai et al described a case of rapidly progressive glomerulonephritis following Alectinib initiation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations